LOKAKARYA FUN LEARNING DENGAN FLOW, GRIT & GROWTH MINDSET [FUN LEARNING WORKSHOP WITH FLOW, GRIT & GROWTH MINDSET] - Ihan Martoyo; Marincan Pardede; Julinda Pangaribuan; Mario Gracio A. Rhizma; Henri Putra Uranus; Junita Junita; Herman Kanalebe; Rocky T. Putra; Heri Yulian; Rianto Mangunsong; Rosmaya Nainggolan (Universitas Pelita Harapan, 2018)
Three theories in educational psychology: (1) Flow (Mihaly Csikszentmihalyi), (2) Grit (Angela Duckworth), dan (3) Growth mindset (Carol Dweck) open the possibility for fun learning. Flow according to Csikszentmihalyi happens when the challenge in an activity is balanced with the necessary skill, so that one can experience flow during the activity. This feeling of flow is actually what makes learning fun. The concept of grit consists of two components: (1) perseverance and (2) passion for long term goals. Duckworth discovered that grit can predict success better than mere intellect (IQ). Growth mindset is a psychological state where one is not afraid to look stupid and therefore is more open to challenges because he/she focuses more on the learning process rather than momentary results. In the workshop in one private school in Tangerang, the three concepts were explained with concrete examples from movies and other illustrations. Furthermore, we did a demonstration in optical physics with simple equipments to simulate natural phenomena: A rainbow, the red evening sky, and laser deflection due to refractive index difference. Pre-test and post-test results after the fun learning workshop show that the concept of flow and grit is easier to comprehend by the teachers than growth mindset. After the workshop, there is an increase in the opinion that math and physic lessons can also be fun.